Exploring the efficiency and emission characteristics of hydroxy-boosted canola biodiesel in comparison to traditional diesel fuels - Çalık, Ahmet (Frontiers in Energy Research, 2024)
In this research, we experimentally examined how incorporating HHO into blends of 20% canola biodiesel with 80% diesel and 40% canola biodiesel with 60% diesel impacts the engine's performance and its emission traits. Canola oil, widely used in Europe, served as the biodiesel base. The addition of HHO, recognized for its potential to improve combustion efficiency and reduce emissions which were deteriorated by biodiesel addition. The findings revealed decrement on fuel consumption as 5.74% and 4.43% and rise in thermal efficiencies as 3.92% and 3.97% with HHO addition compared to B20 and B40, respectively. Besides that, CO emissions were reduced significantly up to 35.43%, while CO2 emissions decreased moderately up to 14.93% compared to diesel fuel. On the other hand, biodiesel and HHO addition increased NOx emissions as 49.80%. Utilization of biodiesel and HHO in diesel engines offers a straightforward way to reduce emissions and enhance fuel efficiency, addressing environmental issues and promoting sustainable transportation.